Dynamic responses of picophytoplankton to physicochemical variation in the eastern Indian Ocean. Issue 8 (1st April 2019) - Wei, Yuqiu; Zhang, Guicheng; Chen, Ju; Wang, Jing; Ding, Changling; Zhang, Xiaodong; Sun, Jun
Abstract: Picophytoplankton were investigated during spring 2015 and 2016 extending from near‐shore coastal waters to oligotrophic open waters in the eastern Indian Ocean (EIO). They were typically composed of Prochlorococcus ( Pro ), Synechococcus ( Syn ), and picoeukaryotes ( PEuks ). Pro dominated most regions of the entire EIO and were approximately 1–2 orders of magnitude more abundant than Syn and PEuks . Under the influence of physicochemical conditions induced by annual variations of circulations and water masses, no coherent abundance and horizontal distributions of picophytoplankton were observed between spring 2015 and 2016. Although previous studies reported the limited effects of nutrients and heavy metals around coastal waters or upwelling zones could constrain Pro growth, Pro abundance showed strong positive correlation with nutrients, indicating the increase in nutrient availability particularly in the oligotrophic EIO could appreciably elevate their abundance. The exceptional appearance of picophytoplankton with high abundance along the equator appeared to be associated with the advection processes supported by the Wyrtki jets. For vertical patterns of picophytoplankton, a simple conceptual model was built based upon physicochemical parameters. However, Pro and PEuks simultaneously formed a subsurface maximum, while Syn generally restricted to the upper waters, significantly correlating with the combined effects of temperature, light, and nutrient availability. The average chlorophyll a concentrations (Chl a ) of picophytoplankton accounted for above 49.6% and 44.9% of the total Chl a during both years, respectively, suggesting that picophytoplankton contributed a significant proportion of the phytoplankton community in the whole EIO. Abstract : The dynamic responses of picophytoplankton abundance and distribution to physicochemical conditions associated with circulations and water masses were investigated by using FCM to address the lacking data of picophytoplankton and to understand the effects of annually ambient variations on picophytoplankton in the EIO.